Playful strategies for critical-creative thinking in five-year-old children - Linares, Wendy (2022)
This research aimed to develop a model of playful strategies for the development of critical and creative thinking in 5-year-old children from the Educational Institution No. 284 of Bagua Grande, Amazonas region, Peru. The research was purposeful because the playful strategies model was formulated to develop these two thoughts. The data was collected through a test applied to 25 5-year-old children in the classroom and an interview guide for the teacher in charge of the school. As a result, it was found that more than 80% of the population presented a low level of critical and creative thinking in all its dimensions and that teachers do not use adequate strategies to promote these thoughts during the teaching-learning process. Therefore, it was concluded that playful strategies are valuable tools to develop critical and creative thinking in 5-year-old preschool children.